Difusi Inovasi Hutan Wisata Limpakuwus Melalui Pengembangan Masyarakat Berbasis Aset: Studi di Koperasi Jasa Hutan Pinus Limpakuwus - Winata, Indra; Yusdiana, Devie; Suhati, Lisafani; Delimasari Piliang, Fitri (Koaliansi : Cooperative Journal, 2023)
One of the efforts to boost the village economy can be done by carrying out development based on the resources they have, be it natural resources, culture, local wisdom or uniqueness. Because a village that has the ability to utilize all its resources will be able to develop as an innovative and educative tourism village. The process of diffusion of innovation that occurred in Limpakuwus Village is proof that the ability and willingness of local residents to utilize all their resources has made the area a tourist village that has an attraction for tourists to visit and enjoy the atmosphere in the Limpakuwus Tourism Forest. This research was conducted with the aim of providing an overview and insight for the parties that the process of diffusion of innovations in tourism villages can be carried out using an asset-based community development model, so that this model can be applied in other regions. The existence of awareness and shared needs among the people of Limpakuwus Village in order to increase income and welfare, can be realized through collaboration in a cooperative movement forum with the name Pinus Limpakuwus Forest Services Cooperative